1996
DOI: 10.1007/bf02002722
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy presenting clinicopathological features of acute post-streptococcal glomerulonephritis

Abstract: These results suggest that in some patients, IgA nephropathy may be triggered by streptococcal infection and misdiagnosed as acute post-streptococcal glomerulonephritis if renal histological examinations are not done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Several reports have concerned IgA nephropathy superimposed by PSGN or PIGN [3][4][5][6][7][8][9]. The incidences of IgA nephropathy and PSGN/PIGN are relatively high, but no relationship between their pathogenesis is known.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports have concerned IgA nephropathy superimposed by PSGN or PIGN [3][4][5][6][7][8][9]. The incidences of IgA nephropathy and PSGN/PIGN are relatively high, but no relationship between their pathogenesis is known.…”
Section: Discussionmentioning
confidence: 96%
“…The presence of a fibrous crescent in the biopsy specimen suggested that the disease antedated the PSAGN, and the latter could have activated cellular immunity and augmented renal tissue injury [5]. Patients with similar presentation, although rare, have been reported earlier [6,7].…”
Section: Discussionmentioning
confidence: 96%
“…The presence of S. pyogenes in the biopsy of the control patient with IgA nephropathy may be coincidental. A connection between IgA nephropathy and post-streptococcal glomerulonephritis in some cases is suggested in the literature [34,35 ]. This may also be the case in Hennoch-Schönlein´s purpura, a disease related to IgA nephropathy [36].…”
Section: Discussionmentioning
confidence: 97%